PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET, DAN TOTAL ASSET TURNOVER TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009 - 2011 (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of Debt To Equity Ratio, Return on Assets, and Total Assets Turnover on Stock Price at a manufacturing company in BEI period 2009-2011. The population used in this study is a manufacturing company that is going public for 3 years from the year 2009 to 2011. The samples selected by purposive sampling obtained 93 issuers. The method of analysis used in this study is that by using multiple linear regression method, requies normality test, the classical assumption examination which consist of multicollinearity test, heteroscedasticity test, and autocorrelation test and strength test models consisting of: coefficient of determination test and F test. Hypothesis testing using t-statistic. The results of this study indicate that Debt To Equity Ratio is significant positive effect, Return on Assets is significant positive effect on stock price. While the Total Asset Turnover is significant positive effect on stock price.Keywords: Debt To Equity Ratio, Return On Asset, Total Assets Turnover, Stock Price